2014
DOI: 10.3389/fnsyn.2014.00024
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the role of cholinergic signaling in circuits of attention and emotionally salient behaviors

Abstract: Acetylcholine (ACh) signaling underlies specific aspects of cognitive functions and behaviors, including attention, learning, memory and motivation. Alterations in ACh signaling are involved in the pathophysiology of multiple neuropsychiatric disorders. In the central nervous system, ACh transmission is mainly guaranteed by dense innervation of select cortical and subcortical regions from disperse groups of cholinergic neurons within the basal forebrain (BF; e.g., diagonal band, medial septal, nucleus basalis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 119 publications
(186 reference statements)
2
45
0
Order By: Relevance
“…The current in vivo electrophysiological studies also provide support to the notion that ACh can act rapidly and exert prolonged changes in network excitability (Chen et al 2015, Eggermann et al 2014, Luchicchi et al 2014, Sarter et al 2014). In the BLA brief photo-activation of cholinergic terminal fields elicited rapid changes in action potential firing (τ delay = 62 msec; Fig 3D) or in membrane potential (τ delay =10–100 msec) and slower but prolonged increases in firing rates of putative principal neurons (Fig 3, 4).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The current in vivo electrophysiological studies also provide support to the notion that ACh can act rapidly and exert prolonged changes in network excitability (Chen et al 2015, Eggermann et al 2014, Luchicchi et al 2014, Sarter et al 2014). In the BLA brief photo-activation of cholinergic terminal fields elicited rapid changes in action potential firing (τ delay = 62 msec; Fig 3D) or in membrane potential (τ delay =10–100 msec) and slower but prolonged increases in firing rates of putative principal neurons (Fig 3, 4).…”
Section: Discussionsupporting
confidence: 62%
“…Recall of either highly aversive or appetitive events engages distributed brain networks whose activity is tuned by various neuromodulators, including acetylcholine (ACh; (Hasselmo and Sarter 2011, Hermans et al 2014, LeDoux 2012, Luchicchi et al 2014, Picciotto et al 2012). Cholinergic signaling has long been implicated in attending to and remembering emotionally potent experiences, but the precise role of ACh signaling in mnemonic processing of highly salient events has remained elusive (Dani and Bertrand 2007, Hasselmo and Sarter 2011, Luchicchi et al 2014, Sarter et al 2014). The major challenge to dissecting the role of endogenous ACh in the formation and retention of potent memories has been the inability to selectively and reversibly manipulate the activity of cholinergic inputs, which tend to be sparsely distributed, extensively arborized and intermingled with projections of other transmitter phenotypes (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the recent studies that have demonstrated a central role of cholinergic signaling in both attentional and memory related circuits and behaviors have been made possible by the advent of optogenetics for the selective stimulation of BF cholinergic neurons and their terminal fields (Jiang et al, 2014; Luchicchi et al, 2014). An additional benefit of the technology is its illumination (pun intended) of the extent to which many transmitters – including ACh - are co-stored and, under some stimulation conditions, may be co-released with other transmitters (e.g.…”
Section: Cholinergic Signaling and Circuits Involved In Attention mentioning
confidence: 99%
“…; Luchicchi et al . ). However, recent evidence suggests that ACh can be a primary driver of activity, complementing glutamate (Beierlein, ; Sarter et al .…”
Section: Introductionmentioning
confidence: 97%